Internal seiches as drivers of fish depth use in lakes. Issue 5 (11th March 2022) - Brooks, Jill L.; Midwood, Jonathan D.; Smith, Adam; Cooke, Steven J.; Flood, Bryan; Boston, Christine M.; Semecsen, Patricia; Doka, Susan E.; Wells, Mathew G.
Abstract: Inland temperate lakes undergo various physical processes, such as thermal stratification, that dictate the spatial availability of suitable temperature and dissolved oxygen conditions. Here, we use intensive limnological monitoring and acoustic telemetry transmitters implanted in wild fish to document the magnitude and frequency of thermocline deflection events (i.e., wind driven internal seiches that lead to upwelling of hypoxic hypolimnetic water) and their influence on freshwater fish depth use in a coastal embayment of Lake Ontario. The embayment experienced around 100 internal seiche events during a 3‐month period and tracking of walleye ( Stizostedion vitreus ) vertical positions in the water column showed clear trends of avoidance of low dissolved oxygen. Quantile regression showed a significant correlation between walleye vertical position and the depth of the 3, 4, and 5 mg L −1 oxyclines, with the 3 mg L −1 oxycline having the largest effect. Upwellings of the hypoxic hypolimnion forced walleye to use the water column above these fluctuating oxyclines (5 th percentile, p < 0.001), with 94.2% of detections occurring at depths above the 3 mg L −1 oxycline. Understanding how fish respond to upwelling events (both temperature and oxygen) is important for fisheries assessment, management, and habitat restoration planning as there is clear avoidance of suboptimal oxygen conditions and sampling in the overcrowded fringes of these low‐oxygen zones could artificially inflate population estimates.